Effect of Mg alloying and cooling rate on the microstructure of silicon - Zhu, Mengyi; Safarian, Jafar; Irvansyah, Mochamad Ilham Al Fariesy; Di Sabatino, Marisa (Frontiers in Photonics, 2024)
In response to the escalating global demand for solar photovoltaic (PV) energy, there is a critical need for more cost-effective and environmentally sustainable production methods for upgrading metallurgical grade silicon (MG-Si). Among various metallurgical approaches, acid leaching is an economical and effective method to upgrade the MG-Si. However, the impact of cooling rates during solidification, a potentially significant factor for the optimization of the leaching process, has been rarely investigated. In this work, the effects of magnesium alloying content and cooling rate on the microstructural evolutions in MG-Si are studied. MG-Si was alloyed with two different magnesium contents (5.5 wt% and 9.0 wt%), utilizing an induction furnace for the melting, alloying, and casting process. The cast alloys were subsequently remelted under five distinct cooling rates, specifically 3, 10, 25, 40, and 80 °C/min. Microstructural analysis and grain size measurement were conducted using Scanning Electron Microscopy (SEM), Electron Backscatter Diffraction (EBSD), and the ASTM E112 standards. It was observed that Mg2Si phase was formed along the primary Si grains and with other intermetallic silicide containing impurities embedded inside. Moreover, higher cooling rates resulted in finer primary Si grains with a highly diverse crystallographic orientations, while slower rates induced coarser Si grains and concentrated silicide phase along the grain boundaries. Importantly, the results also indicate that a higher magnesium alloying content (9.0 wt%) led to finer grain sizes. The present work establishes links between alloying content, cooling rate, and the resulting microstructure, offering valuable insights for optimizing the alloying-leaching process.